2015
DOI: 10.1016/j.eats.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transverse Lateral Retinaculum Reconstruction for Medial Patellar Instability

Abstract: Medial patellar instability can be a disabling complication of an extensive lateral retinaculum release. It is often overlooked, and for the diagnosis, it is necessary to have a high index of suspicion. Typically, the patient feels a new pain and new instability after the lateral retinaculum release that are distinct from, and much worse than, those before surgery. All of our patients had significant relief from their pain with "reverse" McConnell taping. If there is a significant improvement in symptoms after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This study showed no pathological findings. Extensive LRR might lead to iatrogenic medial patellar instability or a patellar multidirectional instability that would require a reconstruction of the lateral patellar retinaculum[ 24 - 26 ].…”
Section: Failed Mpfl Reconstruction Due To An Incorrect Assessment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed no pathological findings. Extensive LRR might lead to iatrogenic medial patellar instability or a patellar multidirectional instability that would require a reconstruction of the lateral patellar retinaculum[ 24 - 26 ].…”
Section: Failed Mpfl Reconstruction Due To An Incorrect Assessment Ofmentioning
confidence: 99%
“…Also in cases where an extensive LRR had been performed, a reconstruction of this lateral retinaculum would be necessary[ 26 ]. This surgery should only be performed after a detailed radiological assessment of medial patellar instability.…”
Section: Failed Mpfl Reconstruction Due To An Incorrect Assessment Ofmentioning
confidence: 99%
“…In patients who have had prior lateral releases, multiple reconstructive techniques have been described, which could perhaps be utilized in place of a dermal allograft. For example, Sanchis-Alfonso et al 16,17 described performing a deep transverse lateral retinaculum reconstruction using an anterior strip of the iliotibial band for patients with medial The medial patellofemoral ligament graft is then shuttled with a hemostat under the retinaculum and sequentially inserted into the femoral tunnel that was created at Schottle's point using a guide pin followed by a reamer that is 1 mm in diameter larger than the graft diameter. Intraoperative image of the left knee of the patient positioned supine on the operating table with the foot of the bed lowered and the nonoperative extremity in lithotomy position.…”
Section: Discussionmentioning
confidence: 99%
“…29 Lateral patellofemoral ligament (LPFL) reconstruction is one treatment option for patients with iatrogenic medial instability secondary to lateral retinacular release that has demonstrated improved patient outcomes in multiple case series. 3,4,21,22,34 To successfully perform an LPFL reconstruction, a comprehensive understanding of the LPFL anatomy and biomechanics is required. In addition, a better understanding of the accessory lateral stabilizers, including the lateral patellomeniscal ligament (LPML) and lateral patellotibial ligament (LPTL), may lead to development and evolution in the surgical reconstruction of these structures, analogous to how the medial patellotibial ligament (MPTL) can be reconstructed in isolation or in addition to a medial patellofemoral ligament (MPFL) reconstructions which have been shown to improve outcomes in specific patient cohorts.…”
mentioning
confidence: 99%